Comparative acoustic performance and mechanical properties of silk membranes for the repair of chronic tympanic membrane perforations. (December 2016) - Allardyce, Benjamin J.; Rajkhowa, Rangam; Dilley, Rodney J.; Xie, Zhigang; Campbell, Luke; Keating, Adrian; Atlas, Marcus D.; von Unge, Magnus; Wang, Xungai
Abstract: The acoustic and mechanical properties of silk membranes of different thicknesses were tested to determine their suitability as a repair material for tympanic membrane perforations. Membranes of different thickness (10–100 μm) were tested to determine their frequency response and their resistance to pressure loads in a simulated ear canal model. Their mechanical rigidity to pressure loads was confirmed by tensile testing. These membranes were tested alongside animal cartilage, currently the strongest available myringoplasty graft as well as paper, which is commonly used for simpler procedures. Silk membranes showed resonant frequencies within the human hearing range and a higher vibrational amplitude than cartilage, suggesting that silk may offer good acoustic energy transfer characteristics. Silk membranes were also highly resistant to simulated pressure changes in the middle ear, suggesting they can resist retraction, a common cause of graft failure resulting from chronic negative pressures in the middle ear. Part of this strength can be explained by the substantially higher modulus of silk films compared with cartilage. This allows for the production of films that are much thinner than cartilage, with superior acoustic properties, but that still provide the same level of mechanical support as thicker cartilage. Together, these in vitro results suggest that silk membranes may provide good hearing outcomes while offering similar levels of mechanical support to the reconstructed middle ear. Graphical abstract: Highlights: Silk membranes were tested as potential tympanic membrane graft material. Silk had higher acoustic amplitude than cartilage suggesting good hearing outcomes. Silk showed good air pressure resistance, which may help resist retraction in vivo.